2019
DOI: 10.1177/1369433219884457
|View full text |Cite
|
Sign up to set email alerts
|

Influence of concrete mix proportions on axial performance of concrete-filled steel tubes made with self-compacting concrete

Abstract: Self-compacting concrete is quite commonly used in concrete-filled steel tube structures, but the compaction level of the self-compacting concrete, that is, the percentage of volume occupied by materials other than air void, within the steel tube is seldom investigated. The authors are of the view that the concrete mix proportions of the self-compacting concrete may have significant effects on the compaction level of the self-compacting concrete, which will be quantified by the ‘compaction index’ proposed in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Ouyang et al studied the effect of mixed proportions of self-compacting concrete on behaviour of concretefilled steel tubular columns under compression. ey found that the post-peak behaviour and ductility of the columns were influenced by paste volume and aggregate proportions [19]. Yu et al studied the behaviours of self-compacting concrete-filled steel tubular columns under eccentric compression.…”
Section: Introductionmentioning
confidence: 99%
“…Ouyang et al studied the effect of mixed proportions of self-compacting concrete on behaviour of concretefilled steel tubular columns under compression. ey found that the post-peak behaviour and ductility of the columns were influenced by paste volume and aggregate proportions [19]. Yu et al studied the behaviours of self-compacting concrete-filled steel tubular columns under eccentric compression.…”
Section: Introductionmentioning
confidence: 99%